Systemic Lymphadenectomy Cannot Be Recommended for Low-Risk Corpus Cancer - Takao Hidaka; Akitoshi Nakashima; Tomoko Shima; Toru Hasegawa; Shigeru Saito (Obstetrics and Gynecology International)
Objective. The objective of this study is to ascertain whether omission of lymphadenectomy could be possible when uterine corpus cancer is considered low-risk based on intraoperative pathologic indicators. Patient and Methods. Between 1998 and 2007, a total of 83 patients with low risk corpus cancer (endometrioid type, grade 1 or 2, myometrial invasion ≦50%, and no intraoperative evidence of macroscopic extrauterine spread, including pelvic and paraaortic lymph node swelling and adnexal metastasis) underwent the total abdominal hysterectomy and bilateral salpingo-oophorectomy without lymphadenectomy. A retrospective review of the medical records was performed, and the disease-free survival (DFS), overall survival (OS), peri- and postoperative morbidities and complications were evaluated. Results. The 5-year DFS rates and the 5-year OS rates were 97.6% and 98.8%, respectively. No patient presented postoperative leg lymphedema and deep venous thrombosis. Conclusion. Omission of lymphadenectomy did not worsen the DFS or OS. The present findings suggest that systemic lymphadenectomy could be omitted in low-risk endometrial carcinoma.